2001 Proceedings. 51st Electronic Components and Technology Conference (Cat. No.01CH37220)
DOI: 10.1109/ectc.2001.927944
|View full text |Cite
|
Sign up to set email alerts
|

Underfilled BGAs for a variety of plastic BGA package types and the impact on board-level reliability

Abstract: There are continuous efforts in the electronics industry to reduce electronic package size. The main force pushing for smaller package size is the desire by original equipment manufacturers to reduce their mother board size and thereby their own costs. Reducing the size of electronic packages can be achieved by a variety of means and for ball grid array (BGA) packages an effective method is to decrease the pitch between the individual balls. Reducing the pitch between balls decreases the ball size and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Finally, indeed, the CTE is also very critical to the thermomechanical fatigue performance; generally speaking, the underfill with a CTE close to that of a typical mold compound and PCB laminate can minimize the in-plane shear loads applied to the solder joint. [24][25][26][27][28][29] However, its effect is not so obvious in this study owing to the similar CTEs of the underfills used.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, indeed, the CTE is also very critical to the thermomechanical fatigue performance; generally speaking, the underfill with a CTE close to that of a typical mold compound and PCB laminate can minimize the in-plane shear loads applied to the solder joint. [24][25][26][27][28][29] However, its effect is not so obvious in this study owing to the similar CTEs of the underfills used.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…This is even more true for lead-free assemblies than for eutectic-SnPb soldered assemblies. [24][25][26][27][28][29] In this paper, we discuss the thermomechanical fatigue performance of chip scale packages (CSPs) with FCFUs and PCFUs used in conjunction with lead-free solder (solder paste and solder balls on the CSP). The assemblies without underfills were also tested for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 32) systematically analyzed the effects of underfill thermomechanical properties on the thermal cycling fatigue reliability of flip chip BGA using a steady-state creep model, they found by calculation that an underfill with a high modulus, a high T g , and a low CTE is best for thermal fatigue performance, while an underfill with a high modulus, a low T g , and a low CTE is worst. Burnette et al 33) evaluated the board-level reliability of a variety of plastic BGAs with underfills. Their parametric study based on a valid finite element model showed that the optimum underfill material would have a CTE of approximately 15 ppm/ C, but that its modulus could range between 2 and 10 GPa without obvious effects on the thermal cycling reliablity.…”
Section: Effects Of Dispensing Patterns On the Thermal Cyclingmentioning
confidence: 99%